# m+6n-m+n-5+6n+3m=

## Simple and best practice solution for m+6n-m+n-5+6n+3m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for m+6n-m+n-5+6n+3m= equation:

Simplifying
m + 6n + -1m + n + -5 + 6n + 3m = 0

Reorder the terms:
-5 + m + -1m + 3m + 6n + n + 6n = 0

Combine like terms: m + -1m = 0
-5 + 0 + 3m + 6n + n + 6n = 0
-5 + 3m + 6n + n + 6n = 0

Combine like terms: 6n + n = 7n
-5 + 3m + 7n + 6n = 0

Combine like terms: 7n + 6n = 13n
-5 + 3m + 13n = 0

Solving
-5 + 3m + 13n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 3m + 5 + 13n = 0 + 5

Reorder the terms:
-5 + 5 + 3m + 13n = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 3m + 13n = 0 + 5
3m + 13n = 0 + 5

Combine like terms: 0 + 5 = 5
3m + 13n = 5

Add '-13n' to each side of the equation.
3m + 13n + -13n = 5 + -13n

Combine like terms: 13n + -13n = 0
3m + 0 = 5 + -13n
3m = 5 + -13n

Divide each side by '3'.
m = 1.666666667 + -4.333333333n

Simplifying
m = 1.666666667 + -4.333333333n`